The influence of the anthropometric characteristics and handgrip strength on the technical skills of young basketball players - Apostolidis, N.; Zacharakis, E. (Journal of Physical Education and Sport, 2015)
In basketball game the young players involved with the sport, should be discriminated by particular anthropometric characteristics and technical skills. The aim of the present study was to confirm the relationship between anthropometric characteristics, handgrip strength and selected technical skills and mainly to establish a simple prediction model of these technical skills through the most significant anthropometric parameters. Due to this purpose 106 young basketball players 13-14 years old with minimum training experience of two years were measured in six longitudinal measures (body height, stretched arms` length, upraised arms` length, upper arm`s length, forearm`s length and hand`s circumference), body mass, handgrip strength and four basketball skill tests of speed dribble, obstacle dribble, speed spot shooting and free throws performance. The results of the regression analysis and the canonical correlation analysis indicated significant predictability of handgrip strength, stretched arms length, body height, and upraised arms height on speed and obstacle dribble, indicating the influence of these anthropometric parameters on basketball handling ability. Conclusively, the measured anthropometric characteristics of the young basketball players are considered crucial for their basketball game capability. Therefore, coaches involved with training procedure of the specific ages, should take these results under consideration, in order to recruit the most skilled players and facilitate the classification of them on the playing positions.